2013
DOI: 10.1186/1471-2180-13-240
|View full text |Cite
|
Sign up to set email alerts
|

MazF6 toxin of Mycobacterium tuberculosis demonstrates antitoxin specificity and is coupled to regulation of cell growth by a Soj-like protein

Abstract: Background: Molecular programs employed by Mycobacterium tuberculosis (Mtb) for the establishment of non-replicating persistence (NRP) are poorly understood. In order to investigate mechanisms regulating entry into NRP, we asked how cell cycle regulation is linked to downstream adaptations that ultimately result in NRP. Based on previous reports and our recent studies, we reason that, in order to establish NRP, cells are halted in the cell cycle at the point of septum formation by coupled regulatory mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 52 publications
5
32
0
Order By: Relevance
“…Consistent with observations of other TA systems, we also observed relative abundance of mazF transcripts in comparison with mazE transcripts (Fig. 1c-e) 32,41,42 . Compared with early log phase bacteria, no differences were observed in the transcript levels of mazE3, mazF3, mazE6, mazF6, mazE9 and mazF9 in mid-log and late-log growth stages (Fig.…”
Section: Expression Of Mazf3 Mazf6 and Mazf9 Inhibit Mtb Growthsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with observations of other TA systems, we also observed relative abundance of mazF transcripts in comparison with mazE transcripts (Fig. 1c-e) 32,41,42 . Compared with early log phase bacteria, no differences were observed in the transcript levels of mazE3, mazF3, mazE6, mazF6, mazE9 and mazF9 in mid-log and late-log growth stages (Fig.…”
Section: Expression Of Mazf3 Mazf6 and Mazf9 Inhibit Mtb Growthsupporting
confidence: 92%
“…These differences in the transcript levels may be attributed to the differential stability of the transcripts or the expression of mazF is driven from multiple promoters. Similar post-transcriptional regulation of TA modules has also been observed in E. coli and during infection of macrophages and mice with Mtb 32, 41,42 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several models supporting the different functions of the TA system in bacterial physiology have been proposed, including a programmed cell death model, growth-modulation model, persistence model, development model and stress tolerance module Gerdes and Maisonneuve, 2012;Van Melderen and Saavedra De Bast, 2009). In spite of the different functions that have been proposed, increasing evidence has demonstrated that TA systems encoded by chromosomes are stress-response loci that can impact overall cell physiology and help cells to cope with various stresses under unfavorable conditions (Buts et al, 2005;Pandey and Gerdes, 2005;Ramirez et al, 2013;Soo and Wood, 2013;Tamman et al, 2013). One group has reported that TA loci are highly abundant in free-living prokaryotes, whereas obligate intracellular organisms are devoid of these loci (Pandey and Gerdes, 2005).…”
Section: Mazef Bif Is Activated Under Conditions Of Acid Stressmentioning
confidence: 97%
“…Because TA systems participate in the stress responses of E. coli, Mycobacterium tuberculosis and Pseudomonas putida (Ramirez et al, 2013;Tamman et al, 2013;Van Melderen and Saavedra De Bast, 2009), it can be postulated that those in bifidobacteria might act as important stress-response elements. Whether there are functional TA systems in bifidobacterial chromosomes and what roles they play in cellular responses to environmental challenges have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%